Comparison of arsenate adsorption from neutral pH aqueous solutions using two diferent iron‑trimesate porous solids: kinetics, equilibrium isotherms, and synchrotron X‑ray absorption experiments - Berardozzi, Eliana (2020)
We have explored the use of two different iron-based porous materials for arsenic uptake from neutral pH aqueous solutions. Both materials are reminiscent of a material known as MIL-100(Fe), a Metal Organic Framework (MOF) built upon the coordination of Fe(III) ions with trimesate organic linkers (benzene tricarboxylic acid). Aside from the proverbial high surface area with extended microporosity/mesoporosity, the presence of Fe(III) centers offers the possibility of specific strong interactions with arsenic, therefore making it appealing for its use in detection and purification technologies. Our approach tackles the characterization of the system from both physical and chemical perspectives. We report equilibrium isotherms and time dependent arsenic uptake for the determination of adsorption capacity and kinetics; and also, by means of synchrotron-based X-ray absorption techniques, we probe possible changes in coordination environments and oxidation states of Fe and As in the porous network occurring upon adsorption at high and low loadings. The results presented bring further insight on the nature and diversity of adsorption sites present and confirm the suitability of the proposed adsorbents for the intended use.